Experimental Study on Working Characteristics of Microwave-Assisted Spark Plug Igniter - Hao Zeng; Changqin Fu; Zhiyu Zhao; Nan Jiang; Zhihao Liu (Fire, 2025)
In this paper, a study on the working characteristics of microwave-assisted spark plug igniter was carried out. Experiments were carried out in a vacuum chamber to investigate the effects of microwave feeding with different parameters on the spark plug discharge process, breakdown voltage, average power, discharge spectral intensity, and characteristic temperature of the discharge plasma under different ambient pressures (0.1 MPa at atmospheric pressure and 0.05 MPa at low pressure). The results show that the breakdown voltage decreased by 15.2% and the average power of discharge increased by 49% when the microwave pulse peak power increased from 0 W to 200 W under a low-pressure environment; meanwhile, the breakdown voltage decreased by 10.8% and the average power increased by 23% under an atmospheric-pressure environment. When the microwave pulse frequency was increased from 1 kHz to 10 kHz, the breakdown voltage further decreased by 15.2% in a low-voltage environment, but there was no significant effect on the average power. The plasma characteristic temperature rose significantly with the peak power: the electron temperature rose from 1.961 eV to 2.154 eV with the power at atmospheric pressure, and the vibrational and rotational temperatures also increased significantly.